Evoked potentials predict psychomotor development in neonates with normal MRI after hypothermia for hypoxic-ischemic encephalopathy. Issue 1 (January 2019) - Cainelli, E.; Trevisanuto, D.; Cavallin, F.; Suppiej, A.
Abstract : Therapeutic hypothermia (TH) for neonatal hypoxic-ischemic encephalopathy (HIE) reduced severe outcomes, however, caution is warranted when prognosticating about neurodevelopment if magnetic resonance imaging (RMI) shows no or minor degrees of brain injury (Rollins et al., 2014). To assess the prognostic role of evoked potentials (EP) in neonates with normal MRI. Thirty-five neonates recruited for TH because of HIE, having normal neonatal MRI, performed neonatal somatosensory (SEP), visual (VEP) evoked potentials and electroencephalogram (EEG). The effect of SEP, VEP or EEG abnormalities on Griffith's developmental scales at 12 and 24 months was measured; positive (PPV) and negative (NPV) predictive value, sensitivity, specificity and accuracy were calculated. At 24 months, VEP abnormality was associated with impaired hearing-language (p = 0.002) and performance score (p < 0.0001). VEP achieved best PPV (0.91) and specificity (0.93). The combination of neurophysiological tests achieved the best NPV (0.85), sensitivity (0.90), accuracy (0.83). Psychomotor sequelae may occur in survivors of neonatal HIE with normal MRI. VEP is the single best neurophysiological prognostic marker but the combination of neurophysiological tests has a better value. When facing the challenge of neurodevelopmental prognosis in infants with normal MRI after TH, EPs are useful prognostic tools, complementary to EEG.